Supermarket nutritionists’ perspectives, views, and experiences on affordability interventions to support healthier and more environmentally sustainable food purchasing in UK retail settings - Stone, Rebecca A; Brown, Adrian; Douglas, Flora; Greatwood, Hannah; Griffiths, Claire; Hunter, Emma; Johnstone, Alexandra Mary; Lonnie, Marta; Morris, Michelle; Skeggs, Hannah; Hardman, Charlotte A. (Frontiers in Nutrition, 2025)
IntroductionFood insecurity (lack of reliable access to affordable and nutritious food) is a major concern in high-income countries because it increases the risk of poor nutrition, obesity and associated adverse health outcomes. Healthier diets are often also more environmentally sustainable (hereafter; sustainable), an important factor in reducing climate change. Practice-based interventions are therefore urgently needed to support people living with food insecurity and obesity to access and afford healthier and sustainable foods. Supermarkets are a key area for intervention, as purchasing can be an antecedent to consumption. However, the retailers’ perspectives on the feasibility of implementing affordability interventions is often overlooked and under-researched. Therefore, this study explored the perspectives, views, and experiences of major UK supermarket senior nutritionists on the acceptability and feasibility of using affordability interventions for healthier and sustainable food in the supermarket.MethodsWe recruited seven UK senior supermarket nutritionists who represented 85% of the UK grocery market share. We used semi-structured interviews and analysed the data using a reflective thematic analysis approach.ResultsSupermarket nutritionists perceived that their business did prioritise health and environmental sustainability for customers. However, there were several challenges encountered when trying to promote healthier and more sustainable food in the supermarket environment, including profitability concerns, unpredictability of intervention outcomes, control over own-brand products, perceived intention-behaviour gap, and a belief that they are already implementing affordability interventions. Differences in how supermarkets approach the evaluation of interventions also emerged, as well as a willingness to collaborate with academics and other retailers to optimise the evaluation of interventions. Lastly, supermarket nutritionists raised the need for an operationalised definition for sustainable food products.DiscussionAffordability interventions to support customers to purchase healthier and more sustainable food require supermarkets to consider multiple challenges. Findings highlight the need for upstream intervention that mandates and facilitates multi-lever approaches to health and sustainability without compromising commercial viability, along with practice-based approaches to implementation and evaluation.